Effect on the Chemical, Structural and Magnetic Characteristics on Fe-Doped srtio3 - (:unkn) unknown (American Scientific Publishers, 2019)
SrTiO3 nanopowders doped with various percentages of Fe (0, 1, 3, and 5 mol%) was synthesized, determining its chemical and structural properties using X-ray diffraction and X-ray photoelectron spectroscopy. The magnetic properties of the samples were studied using hysteresis curves obtained by an alternating gradient magnetometer. Theoretical calculations within the framework of the density functional theory are also performed to support experimental data. The results indicated that Fe incorporated into de SrTiO3 structure induced intrinsic magnetic properties, which increase as the Fe percentage increase. At 5 mol% of Fe in the sample showed a single-domain state, typical of a ferromagnetic material capable for information storage. This latter result would be due to the reduction of oxygen vacancies as more Fe was added and to the presence of Fe2+ and Fe3+ ions reinforced the magnetic behaviour of the compound.